2019
DOI: 10.3389/fmicb.2019.02714
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Membrane Blebs of Brucella abortus 2308 and RB51 and Their Evaluation as an Acellular Vaccine

Abstract: Membrane blebs are released from Gram-negative bacteria, however, little is known about Brucella blebs. This work pursued two objectives, the first was to determine and identify the proteins in the membrane blebs by proteomics and in silico analysis. The second aim was to evaluate the use of membrane blebs of Brucella abortus 2308 and B. abortus RB51 as an acellular vaccine in vivo and in vitro. To achieve these aims, membrane blebs from B. abortus 2308 and RB51 were obtained and then analyzed by liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Previous testing of OMVs purified from B. melitensis and B. abortus as an acellular vaccine in mice, resulted in a level of protection comparable to that obtained from live Brucella vaccines (Avila-Calderón et al, 2012;Araiza-Villanueva et al, 2019). Such results demonstrated that OMVs are not infectious unlike whole Brucella cells, and they elicited a cellmediated protective immune response to kill the intracellular pathogen (Avila-Calderón et al, 2012;Araiza-Villanueva et al, 2019).…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Previous testing of OMVs purified from B. melitensis and B. abortus as an acellular vaccine in mice, resulted in a level of protection comparable to that obtained from live Brucella vaccines (Avila-Calderón et al, 2012;Araiza-Villanueva et al, 2019). Such results demonstrated that OMVs are not infectious unlike whole Brucella cells, and they elicited a cellmediated protective immune response to kill the intracellular pathogen (Avila-Calderón et al, 2012;Araiza-Villanueva et al, 2019).…”
Section: Introductionmentioning
confidence: 84%
“…Differences found in the number of proteins detected in OMVs from B. melitensis 16M could be attributed to the use of different equipment. In 2019, a recent study by Araiza-Villanueva et al (2019) reported 228 proteins identified in OMVs from B. abortus 2308 and 171 in membrane vesicles from the B. abortus rough strain RB51.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations